THE STATUS OF WOMEN IN ROMANIA DURING THE COMMUNIST REGIME. LEGISLATIVE AND CONSTITUTIONAL RIGHTS OF WOMEN (1947 – 1989) - Valentina Tănase (Romanian Journal of Historical Studies)
This study aims to analyze the issue of the status and role of women in Romanian society, during the communist regime, with reference to its legislative and constitutional rights. As women’s emancipation through labor and maternity, represents the feminist conception of that period (the purpose of which was to contest the position of their inferiority, not only legal but also social and cultural), this propaganda message used by the communists is also approached in this study.